PENERAPAN PERENCANAAN PAJAK PADA PT. X DALAM MEMINIMALISASI PAJAK SESUAI PERATURAN PERPAJAKAN - Zulfa, Laili (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
Basically, tax is an important source of revenue to finance government spending, both for routine expenditures and development expenditures. As for corporate, tax is an expense that will reduce the companyâs net profit, so that the management through tax planning schemes. This study aims to identify and learn the implementation of tax planning at PT. X. this study used descriptive qualitative approach and case study metod. The object of this study is the corporate income tax of PT. X with the income statement as a basis for a fiscal correction then resulting in fiscal financial statement and taxable income that will be used for tax planning. The next step is to compare earnings (profit) before tax planning and earnings (profit) after tax planning. The resulting showed that before application of tax planning, tax payable is Rp132.851.711 while after tax planning, tax payable of Rp126.321.378 for the year of 2011. Through good and proper planning, PT. X can optimize their tax to be paid so that it can used to pay for other expenses.Keywords: tax planning, fiscal correction, PPh Pasal 21 allowance (gross up), depreciation of fixassets